AXISYMMETRIC LONGITUDINAL WAVE PROPAGATION IN A FINITE PRESTRAINED CIRCULAR CYLINDER EMBEDDED IN A FINITE PRESTRAINED COMPRESSIBLE MEDIUM - Akbarov, S. D.; Guliev, M. S. (SPRINGER, 2009)
Axisymmetric longitudinal wave propagation in a finite prestrained circular cylinder contained in a finite prestrained infinite body is investigated within the scope of the piecewise-homogeneous body model by employing the three-dimensional linearized theory of elastic waves in a prestressed body. It is assumed that the materials of the cylinder and infinite body are compressible and that their elastic relations are described by a harmonic potential. Numerical results are presented and discussed for the case where the elastic constants of the cylinder are greater than those of the surrounding infinite body
Keywords: axisymmetric wave propagation; finite prestrain; cylinder; wave dispersion; Mechanics